Penerapan Media Pembelajaran Interaktif Pelajaran Bahasa Indonesia Berbasis Android Untuk Kelas Vii Madrasah Tsanawiyah Nahdlatul Wathan Ketangga Sebagai Upaya Untuk Peningkatkan Minat Belajar Siswa - Sudianto, Aris; Samsu, Lalu Muhammad (Infotek : Jurnal Informatika dan Teknologi, 2019)
In today's modern era, the use of computer devices, laptops and smartphones is something that can be said to be a necessity, because the functions of these devices are very helpful in daily activities. In the world of education the role of these devices is very important in the development of better education, with these tools, teaching and learning activities become easier and more enjoyable. The Media of Learning is a medium which was used in a delivery process carried out by someone to another person or between educator and to student. Initially the educator still used the lecture and whiteboard method to be able to deliver Indonesian material to student. This method was an irrelevant method in the sense that the method used was a large amount of energy in delivering an Indonesian language material to students and experiencing saturation by conveying material like this. This method is used before the existence of a computerized or mobile learning media is developing at this time. Therefore the author provides a solution or way to make a computerized or mobile learning media application that is an interactive Indonesian learning media application for Android-based for student of seventh graders which was interesting and fun for the educator and student.DOI : 10.29408/jit.v2i2.1437